The Eastward Spread of Thomas Aquinas' Theological Thought and Its Construction of the Theory of Human Nature in Catholic Theology and Philosophy of the Ming and Qing Dynasties in China - ZHANG, Haoyi; ZHANG, Yongchao (Journal of Research for Christianity in China (JRCC), 2025)
The eastward spread of Thomas Aquinas' theological thought can be regarded as a path of "endogenous construction". It integrated into the internal logic of Catholic theology and philosophy in the Ming and Qing Dynasties of China based on its inherent theories and theological purposes and became a core resource for the construction of this philosophical system. Meanwhile, it was adjusted for localization in combination with the context of traditional Chinese philosophy. Therefore, it played a foundational role in the construction of Catholic theology and philosophy especially the Theory of Human Nature in the Ming and Qing Dynasties of China. Matteo Ricci's Tian Zhu Shi Yi and Giulio Aleni's Xing Xue Cu Shu are typical texts introducing Thomas Aquinas' theological thought. Especially in terms of the theory of soul and the theory of human nature,Tian Zhu Shi Yi basically inherits Aquinas' tradition of natural theology; Xing Xue Cu Shu realizes a systematic introduction to the Aristotelian-Thomistic theory of soul by using the expression of China's native "Xing Xue"; furthermore, Xing Shuo by Xia Dachang, a Confucian Catholic, initially constructed the "spiritual theory of human nature" by "adopting" Aquinas' theory of soul and integrating it with Confucianism's "theory of the goodness of human nature". Regarding the "endogenous construction" of Thomas Aquinas' thought, we need to pay attention not only to its role as a foundational cornerstone but also, more importantly, to its evolutionary characteristics in China and the responses from local scholars.